Determinants of Fiscal Stress in Central Sulawesi 2014-2018 Period - Al-Hadar, Zakina Zein; Ichwan, Mohamad; Yunus, Santi (AFEBI Economic and Finance Review, 2020)
This study aims to analyze the effect the Local-owned Source Revenue, Regional Expenditure and Gross Regional Domestic Product on Fiscal Stress in Regencies/Cities of Central Sulawesi Province Period 2014 – 2018. Data analysis was using panel data regression method. The results of this study indicated that simultaneously variable Local-owned Source Revenue (PAD), Regional Expenditure (BD), and Gross Regional Domestic Product (PDRB) had a significant effect on Fiscal Stress in Regencies/Cities of Central Sulawesi Province for 2014 – 2018 period. Partially, Local-owned Source Revenue variable (PAD) had reduced and significantly decreased Fiscal Stress in the Regency/Cities of Central Sulawesi Province period 2014-2018. Regional expenditure variable (BD) had increase and significantly affected Fiscal Stress in Regencies/ Cities of Central Sulawesi Province Period 2014 – 2018. While Gross Regional Domestic Product (PDRB) variable had increase and was insignificant to Fiscal Stress in Regencies/Cities of Central Sulawesi Province 2014 – 2018 period.